PENINGKATKAN KEMAMPUAN PENGENALAN LAMBANG BILANGAN ANAK USIA 4-5 TAHUN MELALUI MEDIA REALIA - Sibarani, Wilandaoni; Amini, Mukti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This study was conducted to explain the process and results of increasing understanding of symbols and numbers in children aged 4-5 years using realia as a learning tool in grade A1, Rahmani Christian Kindergarten, West Jakarta in 2023. The subjects of the study consisted of ten children. The methods used are qualitative data analysis techniques collected from the results of field notes, observations, interviews, and documentation, and quantitative data analysis techniques collected from the results of the percentage increase in understanding of symbols and numbers in children aged 4-5 years after class actions. This research activity consists of two cycles with five days of activity and five RPPH per cycle. The results showed an increase in each category of children, children's recognition of symbols and numbers had not developed, decreased by 30%, children's recognition of symbols began to develop, experienced management by 43%, children's recognition of symbols and numbers, increased by 40%, and children's recognition of symbols and numbers that developed very well increased by 29%. From these results, it can be seen that the realia method as a learning tool can improve the understanding of symbols and numbers in children aged 4-5 years at Rahmani Christian Kindergarten.